2015
DOI: 10.1186/s12894-015-0081-y
|View full text |Cite
|
Sign up to set email alerts
|

Role for intravesical prostatic protrusion in lower urinary tract symptom: a fluid structural interaction analysis study

Abstract: BackgroundNumerous studies indicated that Intravesical prostatic protrusion is relevant to prognosis of LUTS, however, the confounding effect that is brought about by prostate volume, urethra anterior curvature angle and other factors makes it hard to evaluate the role of intravesical prostatic protrusion in clinical observation.MethodsWe proposed a fluid structural interaction analysis approach. 3D models were constructed based on MRI images, and prostatic urethra diameters were calibrated with urodynamic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 21 publications
0
22
0
2
Order By: Relevance
“…However, these reports did not consider the difference in IPP regarding whether it was the middle lobe, the lateral lobe, or both. A computational fluid dynamic study has shown that IPP predisposed to prostate deformation causes constriction of the prostatic urethra . IPP has been considered to cause a “ball‐valve” effect during voiding .…”
Section: Discussionmentioning
confidence: 99%
“…However, these reports did not consider the difference in IPP regarding whether it was the middle lobe, the lateral lobe, or both. A computational fluid dynamic study has shown that IPP predisposed to prostate deformation causes constriction of the prostatic urethra . IPP has been considered to cause a “ball‐valve” effect during voiding .…”
Section: Discussionmentioning
confidence: 99%
“…Superior to these connections, there is merging with other fascia that leaves the IPP susceptible to the radial component of intravesical pressure, thus leading to prostatic deformation. This study provided further evidence suggesting that IPP influences BOO independently, and that flow deterioration is more resistant to alleviation of obstruction during treatment as the IPP grade increases [7]. …”
Section: Pathophysiology and Clinical Manifestationsmentioning
confidence: 96%
“…A 2015 fluid structural interaction analysis study demonstrated that IPP predisposed the prostate to deformation caused by intravesical pressure. The authors found that the compression of the prostatic urethra and increased variation of cross-sectional area around bladder neck would diminish urine flow efficiency, as well as compromise the effect of obstruction alleviation treatment [7]. Bladder neck and urethral constraint may be due to the nature of the fascia “capsule” surrounding the prostate.…”
Section: Pathophysiology and Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Так, считается, что при больших показателях ИПП вну-трипузырный отдел предстательной железы во вре-мя мочеиспускания может поддаваться радиаль-ному сдавливанию внутрипузырным давлением. Это приводит к сужению простатического отдела уретры и возникновению эффекта «шарового кла-пана», лежащего в основе развития ИВО [17].…”
Section: таблицаunclassified